Penyelesaian Perdata Melalui Perdamaian (Putusan Nomor 305/Pdt.G/2015/PT.Mdn) - R. Vade Rido (Iuris Studia: Jurnal Kajian Hukum, 2020)
Articles 21 and 22 of the Supreme Court Regulation Number 1 of 2008 concerning Mediation Procedures in Courts do not provide many options for resolving civil disputes by disputing parties in the Court. Meanwhile, peace at the level of appeal, cassation and reconsideration is an alternative to dispute resolution that is simple, fast and low cost. This research is descriptive with a normative method, namely by looking at how the integration of mediation as a form of dispute resolution in civil procedural law in Indonesia in resolving civil disputes at the level of appeal, cassation and review. From the results of the research, several obstacles were found in implementing peace at the level of legal remedies with the help of mediators in district courts, so that the parties in the case prefer to settle out of court and withdraw the case in an appeal, cassation or review. Settlement of disputes in a peaceful manner through mediation in the District Court has now become something that must be taken by the disputing parties, this is officially used in the litigation process in the District Court through Perma No. 2 of 2003 concerning Mediation Procedures in Courts